Correlation of Serum 25 Hydroxy Vitamin D and Iron Deficiency Anaemia in Children Attending a South Indian Tertiary Care Hospital: A Cross Sectional Study - Dr. Vadapalli Sri Vaishnavi; Dr Sireesha Patibandla; Satya Ashray Guduru; Dr vijaya lakshmi Ambati (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The molecule 25 hydroxy vitamin D influences the transcription of hepcidin as well as the transportation of iron through the intestines. New research shows that vitamin D deficiency causes iron deficiency anaemia to worsen although studies about this issue remain limited in the Paediatric population of the Indian sub continent. Methods: In a cross sectional study (July 2022–December 2023) we enrolled 350 term children aged 1 month–12 years with haematological criteria for IDA who were attending Niloufer Hospital, Hyderabad. Children with prematurity, haemolysis, chronic inflammatory disease or current vitamin D/iron therapy were excluded. Clinical details, anthropometry, dietary/sun exposure history, and venous samples for complete blood count, iron profile, C reactive protein, calcium and 25(OH)D were obtained. Pearson’s r evaluated correlations; p < 0.05 was significant. Results: Mean age was 3.29 ± 3.0 years; 63.7 % were boys and 71.1 % rural residents. Moderate IDA predominated (78.3 %); 98.6 % had microcytic hypochromic blood pictures. VDD (< 20 ng mL⁻¹) was ubiquitous (94 %; mean 12.3 ± 5.7 ng mL⁻¹). 25(OH)D correlated positively with haemoglobin (r = 0.33, p = 0.036), ferritin (r = 0.56, p = 0.002) and calcium (r = 0.54, p < 0.001). Children with severe VDD (< 10 ng mL⁻¹) had lower mean Hb (7.7 g dL⁻¹) than those with levels > 20 ng mL⁻¹ (9.3 g dL⁻¹; p = 0.001). Conclusion: Nearly all iron deficient children were concomitantly vitamin D deficient, and serum 25(OH)D showed a moderate, significant positive correlation with haemoglobin and ferritin. Our findings support bidirectional links between vitamin D, iron metabolism and calcium homeostasis and justify routine vitamin D screening in paediatric IDA.